Envelhecimento da pele: uma proposta de abordagem investigativa à luz da aprendizagem significativa - Nóbrega, Kayo César Araújo da (2024)
The skin is the largest organ in the human body, whose function is to protect us from environmental elements and contribute to the proper functioning of our body. The first signs of aging appear in this organ, where changes appear that are easily perceived by people. The approach to skin aging as a biological phenomenon is relevant, as it allows a connection with some Biology topics in high school. Therefore, the objective of this study was to promote understanding of this topic among students, with the provision of a didactic sequence manual for teachers and an e-book for basic education students. For this, the research activities were developed with students in the third year of high school at the Escola Normal Estadual Dom Expedito Eduardo de Oliveira, located in Patos-PB, in the academic year of 2023. The research was qualitative in nature and used the research methodology -action, which offers participants the dialogical construction of school knowledge with civic practices. For data collection, resources such as questionnaires, continuous observation with notes in the research professor's logbook, photo records and word clouds were used. The study was developed in two stages, in the first a diagnostic questionnaire was applied and in the second activities were developed in an investigative didactic sequence using active methodologies. The data obtained from the diagnostic questionnaire presented the students' prior knowledge about skin and aging, necessary to identify students' weaknesses on the topic and direct strategies to explore certain topics in more detail in the Investigative Didactic Sequence, including some of the theories that explain the phenomenon of biological aging. The use of diverse teaching strategies enabled the development of skills, from which, through the analysis of images and teaching models, students presented hypotheses to associate the signs and causes of aging with the constituent elements of the skin. Furthermore, the activities developed at SDI were carefully planned to promote meaningful learning, aligned with the inquiry-based teaching approach. For the students, it was an enriching experience, which allowed them to exercise essential skills for scientific training, such as critical thinking, collaboration and communication. Of the proposed activities, case studies made it possible to apply the knowledge developed and exercise autonomy, curiosity and the ability to compare with everyday situations. The research resulted in the production of educational materials that combine theoretical and contextualized knowledge about the anatomy, histology and physiology of young skin and the aging process. The application of the activities validated the theory of meaningful learning and inquiry-based teaching as effective approaches in constructing biological concepts in an attractive and engaging way for students.